Type and size of pollen collected by Tetragonula laeviceps at various altitudes (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Abbas M, Sukarsa. 2022. Type and size of pollen collected by Tetragonula laeviceps at various altitudes. Biodiversitas 23: 1567-1575. Pollen’s type and size are affected by altitude. No study about pollen types and sizes collected Tetragonula laeviceps at various altitudes in Banyumas District, Central Java, Indonesia. This study was aimed to analyze pollen types and sizes collected at various altitudes in Banyumas District. The pollen samples were collected using a random sampling technique at each altitude, namely 46.7 m asl, 317 m asl, and 912 m asl. The pollen samples were collected from flowers around and inside the nest, then prepared using acetolysis. The parameters include pollen morphology, pollen’s polar (P) diameter, and the pollen's equatorial (E) diameter. The morphological characteristics and pollen diameter were analyzed statistically using analysis of variance. Pollens’ type was not affected by altitudes. However, pollen’s diameter was significantly different among altitudes, with the largest pollen size was observed at the highest altitude and the smallest were observed at the lowest altitude. The data are vital for meliponid culture at various altitudes.
Keywords: Diameter, flower, morphology, ornamentation, stingless bee